Maritirukan Aku Bisa: Android application for learning social skills of children with social emotional barriers - S. Suharsiwi; Rd. Heri Solehudin; Erna Budiarti; Noor Azura Zakaria; Siti Rohmah (Universitas Muhammadiyah Malang, 2024)
Android application development for online knowledge dissemination is urgently needed at this time. This study aims to develop an android application for learning social skills of children with social emotional barriers. The research participants consisted of 10 students, 75 respondents including teachers and parents of students in partner schools from Jakarta, Purwokerto, Pekanbaru, and Banjarmasin. The design of the android application was validated by four educational experts from universities. Data were collected through questionnaires and FGDs, and analyzed descriptively. The results obtained are the android application model